2000
DOI: 10.1159/000012071
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Chemotherapy with Vinorelbine and Paclitaxel as Simultaneous Infusion in Advanced Breast Cancer

Abstract: Based on preclinical data showing a synergistic activity of simultaneous administration of vinorelbine and paclitaxel, we carried out a phase II trial in previously untreated advanced breast cancer patients. Treatment consisted of vinorelbine 25 mg/m2 and paclitaxel 150 mg/m2, both drugs given by intravenous infusion over 3 h on day 1, with cycles repeated every 3 weeks. Granulocyte colony-stimulating factor, 300 μg subcutaneously, was given on days 7–12 to the first 10 patients. From Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Since the prophylactic use of G-CSF was not permitted, leucopenia caused frequent reduction/omission, mainly of paclitaxel and/or vinorelbine. The frequency of bone marrow depression observed here did not differ from that reported in other phase II studies testing the association of paclitaxel and vinorelbine (Martin et al, 1998;Tortoriello et al, 1998;Culine et al, 1999;Ellis et al, 1999;Romero Acuna et al, 1999;Vici et al, 2000;Ibrahim et al, 2001;Ballestrero et al, 2003). This suggests that 5-FU may have influenced this side effect only marginally.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Since the prophylactic use of G-CSF was not permitted, leucopenia caused frequent reduction/omission, mainly of paclitaxel and/or vinorelbine. The frequency of bone marrow depression observed here did not differ from that reported in other phase II studies testing the association of paclitaxel and vinorelbine (Martin et al, 1998;Tortoriello et al, 1998;Culine et al, 1999;Ellis et al, 1999;Romero Acuna et al, 1999;Vici et al, 2000;Ibrahim et al, 2001;Ballestrero et al, 2003). This suggests that 5-FU may have influenced this side effect only marginally.…”
Section: Discussioncontrasting
confidence: 51%
“…The combination of paclitaxel and vinorelbine has been evaluated in a number of phase I and II trials. As a whole, the results have been encouraging, with an overall response rate between 47.4 and 67.0% (Martin et al, 1998;Tortoriello et al, 1998;Culine et al, 1999;Ellis et al, 1999;Romero Acuna et al, 1999;Vici et al, 2000;Ibrahim et al, 2001;Ballestrero et al, 2003).…”
mentioning
confidence: 88%
“…We found that the regimen was very active even in patients previously treated with adjuvant or neoadjuvant chemotherapy or having visceral metastases. The toxicity was manageable and compares favorably with that of other regimens (see table 3) [28, 29, 30, 31, 32, 33, 34]. The treatment was administered on an outpatient basis and the majority of patients did not require G-CSF support.…”
Section: Discussionmentioning
confidence: 84%
“…The schedule variable also interacted with the ratio of docetaxel and vinorelbine, suggesting that the ratio was only important if the clinicians chose to intersperse single drug doses between treatments with the combination of drugs (test 8, Table IV). The results of the tests were similar when additional trials, mainly with paclitaxel substituted for docetaxel, were included in the dataset (57,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77).…”
Section: Analysis Of Chemotherapy Clinical Trialsmentioning
confidence: 75%